2018
DOI: 10.1002/rcs.1965
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic sphincter‐preserving total mesorectal excision: A propensity case‐matched analysis

Abstract: Background Robotic total mesorectal excision (R‐TME) is expected to have advantages over laparoscopic total mesorectal excision (L‐TME). The aim is to compare the short‐term outcomes between initial cases of L‐TME and RTME. Materials and methods Among a total of 168 patients assigned to receive either R‐TME (n = 84) or L‐TME (n = 84), short term outcomes were compared between the groups by 1:1 propensity score matching of eight variables. Results The inter‐sphincteric resection rate (42.9% vs. 25%; P = 0.006) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Current study reported that robotic surgery was associated with a lower rate of anastomotic leak than laparoscopic surgery (4.76% vs. 7.36%), which was inconsistent with previous literature [ 8 , 10 , 36 , 38 ] . We found that robotic surgery was with a lower rate of anastomotic leak in only three of the fourteen involved studies [ 24 , 32 , 33 ] , and the both groups showed a significant difference in patient characteristics such as age, tumor distance from anal verge, surgical procedure, and ileostomy. Some of these factors were the independent risk factors of anastomotic leakage [ 42 , 43 ] , which may contribute to this result to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Current study reported that robotic surgery was associated with a lower rate of anastomotic leak than laparoscopic surgery (4.76% vs. 7.36%), which was inconsistent with previous literature [ 8 , 10 , 36 , 38 ] . We found that robotic surgery was with a lower rate of anastomotic leak in only three of the fourteen involved studies [ 24 , 32 , 33 ] , and the both groups showed a significant difference in patient characteristics such as age, tumor distance from anal verge, surgical procedure, and ileostomy. Some of these factors were the independent risk factors of anastomotic leakage [ 42 , 43 ] , which may contribute to this result to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…We routinely perform laparoscopic and robotic TME for locally advanced CRC. 33 The refinement of the surgical technique along with its standardization, better perioperative care, advances in interventional radiology, implementation of multidisciplinary team approach and careful patient selection have helped us to adopt MIS for PE in our center. 9 The magnified view in the pelvis that is narrow and deep, the privilege of executing a meticulous dissection and careful transection of the small branches of internal iliac vessels, the controlled dissection of the distal part of ureters and uretero-vesical junction, and inter-sphincteric space in case of supralevator exenteration have encouraged us to perform more MIS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the mainstay treatment for locally advanced rectal cancer (LARC) is total mesorectal excision (TME), either open or using minimally invasive methods like robotic or laparoscopic surgery [ 3 ]. Compared to the colon, the cancers of the rectum harbor distinct considerations, including the limited space to obtain sufficient margins and to dissect lateral lymph node in the true pelvis [ 3 , 4 ]. Due to these considerations, adjuvant chemoradiation (CRT) has increased the survival of rectal cancer patients and decreased the likelihood of local recurrence (LR).…”
Section: Introductionmentioning
confidence: 99%